Development and Validation of a High-Performance Liquid Chromatography Coupled With Ultraviolet Detection Method for Quantification of Bictegravir in Human Plasma - Xiao, Ran; Fu, Qiang; Chen, Ling; Li, Taisheng; Du, Xiaoli (Therapeutic drug monitoring, 2024)
To establish a method for determining the bictegravir (BIC) concentration in human plasma using high-performance liquid chromatography coupled with ultraviolet detection. The analysis was performed on a CLC-octadecylsilane column (150 × 6.0 mm, 5 μm) using a mixture of phosphate buffer and acetonitrile (62:38, v/v) as the mobile phase at the flow rate of 1.4 mL/min. The column temperature was maintained at 40°C. Using triamcinolone acetonide as the internal standard, 100 μL of plasma sample was extracted by methyl tert-butyl ether, followed by evaporating under nitrogen stream, redissolving with 100 μL mobile phase, and injection of 20-40 μL of supernatant into the chromatographic system. Ultraviolet detection was performed at 260 nm, and the total run time for each sample was 14 minutes. The method exhibited good linearity within the range from 0.10 to 10.0 mcg/mL (r = 0.9995, n = 5). The intraday and interday relative standard deviations for low-, medium-, and high-concentration quality control samples (0.20, 4.00, 8.00 mcg/mL) and the lower limit of quantification (0.10 mcg/mL) were 1.31%-6.20% (n = 10) and 1.18%-2.87% (n = 5), respectively. The intraday and interday accuracies were 100.53%-102.32% and 97.96%-103.84%, respectively. The extraction recovery rates ranged from 80.00% to 88.09% (n = 3). The stability tests showed that the BIC concentration changed by <15%. This study successfully established a high-performance liquid chromatography coupled with ultraviolet detection method for determining plasma BIC concentrations. This method is simple, selective, sensitive, and accurate, making it suitable for clinical monitoring and pharmacokinetic studies of BIC.